Effect of Risk Assessment on Financial Performance of SACCOs in Meru County, Kenya - Kiambi , James Kaimenyi; Mbuba , Susan Kambura; Rintari , Nancy Gacheri (International Journal of Professional Practice, 2023)
In the quest for competitive advantage and higher profitability, financial institutions have focused on accountability. For instance, Savings and Credit Co-operative Societies (SACCOs) have been at the forefront in seeking competitive advantage through enhanced accountability. Effective internal audits help SACCOs to identify and manage risks, improve their operational efficiency, and ensure compliance with regulations and best practices. Despite the presence of internal auditors who review the organization’s internal control systems, some SACCOs experience liquidity problems and loss of funds through non-performing loans. The purpose of this study was to investigate the impact of risks evaluation on the financial outcomes of SACCOs in Meru County, Kenya. The study utilized descriptive survey research. The investigative research focused on 42 SACCOs that have operated in Meru County for a minimum of ten years. The study was a census. Data was gathered through a structured questionnaire. Statistical Package for Social Sciences (SPSS - Version 24) was utilized to analyze data. The researchers used a simple linear regression model and Pearson product-moment correlation to examine the relationship between SACCOs' financial performance and risk assessment. The findings indicated a significant relationship between risk assessment and financial performance of SACCOs in Meru County. It was concluded that effective risk assessment can help SACCOs to reduce operation costs, improve their efficiency, and enhance their financial outcome. The management of SACCOs should implement effective risk assessment policies to mitigate risks, reduce operational costs and enhance financial performance. The findings of this study are anticipated to help SACCO management, the members, and the regulator to appreciate the importance of quality audit systems in minimizing operations costs and mitigating risks.